2011
DOI: 10.1007/s00606-011-0466-7
|View full text |Cite
|
Sign up to set email alerts
|

Genetic structure in fragmented populations of Hippophae rhamnoides ssp. sinensis in China investigated by ISSR and cpSSR markers

Abstract: Hippophae rhamnoides ssp. sinensis is an ecologically and economically important species that has been widely used as a pioneer plant in China. In this study, we employed both nuclear ISSR and maternal cpSSR markers to survey the genetic diversity and structure of populations of ssp. sinensis representing three different landscapes, the northwestern desert and grassland region, the alpine vegetation region of the Qinghai-Tibetan Plateau, and the northeastern humid forest region. In all, 12 natural populations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 32 publications
(29 reference statements)
0
7
0
1
Order By: Relevance
“…This may be attributed to the high degree of vegetative reproduction and spatial isolation of natural populations of H . tibetana , because vegetative reproduction and highly isolated natural populations generally have low genetic diversity within populations [ 60 ], [ 61 ]. Our field observations also indicate that it is common for H .…”
Section: Discussionmentioning
confidence: 99%
“…This may be attributed to the high degree of vegetative reproduction and spatial isolation of natural populations of H . tibetana , because vegetative reproduction and highly isolated natural populations generally have low genetic diversity within populations [ 60 ], [ 61 ]. Our field observations also indicate that it is common for H .…”
Section: Discussionmentioning
confidence: 99%
“…However, in other cases, local adaptation has not been found ( Ometto et al, 2015 ; Hirst et al, 2016 ; Hamann et al, 2017 ). Also the effect of geographical distance and landscape configuration have been documented as an important forces that hinder gene flow and promote genetic differentiation between populations ( Kuss et al, 2008 ; Aægisdóttir et al, 2009 ; Geng et al, 2009 ; Wang et al, 2011 ; De Vriendt et al, 2017 ). However, few studies have combined different isolation processes in the context of landscape genetic approaches (e.g., Mosca et al, 2014 ; Wu et al, 2015 ; Noguerales et al, 2016 ) and focused on environmental variables causing the genetic isolation patters identification (e.g., Manel et al, 2012 ; Mosca et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it binds to glycine receptor for inhabit postsynaptic neurons in CNS of adult . The previous researchers have been reported that the glycine has neuroprotective effects in anoxia, ischemia reperfusion, hypoxia and reactive oxygen species (ROS) . Moreover, glycine is an important amino acid that has multi‐functions in immunity, metabolism, survival, growth and cytoprotection systems in human beings .…”
Section: Introductionmentioning
confidence: 99%